Complete convergence of stochastic approximation algorithm in ℝd under random noises. Issue 2 (2nd April 2016) - Arab, Idir; Dahmani, Abdelnasser
ABSTRACT: In this article, we study a stochastic approximation algorithm that approximates the exact root θ of a function M defined in ℝ d into ℝ d . The function M cannot be known exactly, but only noisy measurements are available at each point x n with the error ξ n . The sequence of noise (ξ n ) n is random; we treat both cases where it is independent and dependent and we establish the complete convergence of the approximated sequence of θ.